2004
DOI: 10.1007/s00775-004-0560-1
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization and peptide-based delivery of magnetic nanoparticles as an intracellular MRI contrast agent

Abstract: We report the development of functionalized superparamagnetic iron oxide nanoparticles with a PEG-modified, phospholipid micelle coating, and their delivery into living cells. The size of the coated particles, as determined by dynamic light scattering and electron microscopy, was found to be between 12 and 14 nm. The PEG-phospholipid coating resulted in high water solubility and stability, and the functional groups of modified PEG allowed for bioconjugation of various moieties, including a fluorescent dye and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
245
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(252 citation statements)
references
References 28 publications
3
245
0
4
Order By: Relevance
“…Although some microemulsion approaches produce nanoparticles that are only soluble in organic solvents, 78 these SPIO can be given water-soluble coatings that prevent agglomeration. 101 It should be noted that while it is generally accepted that microemulsion can produce SPIO with homogeneous sizes, this is dependent on the approach and precision. Further, microemulsion techniques have been criticized as an approach for synthesizing larger nanoparticles due to the formation of SPIO with poor crystallinity.…”
Section: Microemulsionmentioning
confidence: 99%
“…Although some microemulsion approaches produce nanoparticles that are only soluble in organic solvents, 78 these SPIO can be given water-soluble coatings that prevent agglomeration. 101 It should be noted that while it is generally accepted that microemulsion can produce SPIO with homogeneous sizes, this is dependent on the approach and precision. Further, microemulsion techniques have been criticized as an approach for synthesizing larger nanoparticles due to the formation of SPIO with poor crystallinity.…”
Section: Microemulsionmentioning
confidence: 99%
“…This expression accounts for the magnetic field generated by a wire with a uniform magnetization. The angular average convective velocity profile, instead, is defined using a semi-empirical formula, verified by fitting the results of the two dimensional simulations: (8) Where V 0 is the average velocity in the microreactor, Re is the wire Reynolds number (Re= V 0 R w / where and are the density and viscosity of water, respectively), and and are fitting parameters. It was found that a power law dependence of these constants on Peclet number (Pe=V 0 ·R w /D 0 ) was the best option.…”
Section: Simulationmentioning
confidence: 99%
“…In addition, particle surface functionalization is also time consuming due to the purification steps, which are necessary to remove un-reacted reagents and reaction side products. However, standard techniques such as centrifugation or dialysis 7,1,8 often result in irreversible aggregation. Purification by size exclusion chromatography, which is repeated after each surface functionalization step, results in suspension dilution and eventually the loss of NPs in the column.…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic polymers with a low critical micelle concentration (CMC), e.g., Poloxamer ® , Poloxamine ® and lipid-PEG copolymer, can form a stable coating layer around hydrophobic cores [98,114,119]. Amphiphilic polymer coated carbon nanotubes, polystyrene beads, quantum dots, and superparamagnetic iron oxide nanoparticles have been used in in vitro and in vivo applications [17,97,98,114,120,121]. This coating can be generalized for many hydrophobic nanocrystals because it does not rely on the reactivity of the crystal surface [98].…”
Section: Nanoparticle-based Mri and Mr/pet Imaging Contrast Agentsmentioning
confidence: 99%
“…Hydrophobic nanocrystals are usually encapsulated with amphiphilic polymers through a film hydration process [17,97,122,123]. In this method, amphiphilic polymers and nanocrystals are first distributed in a thin film, which is often performed by dispersing all components in chloroform and evaporating the solvent with a rotary evaporator, resulting in a film with uniformly distributed components.…”
Section: Nanoparticle-based Mri and Mr/pet Imaging Contrast Agentsmentioning
confidence: 99%